Preliminary study of the demo plasma separator - Yegorov, A.M.; Yuferov, V.B.; Shariy, S.V.; Seroshtanov, V.A.; Druy, O.S.; Yegorenkov, V.V.; Ribas, E.V.; Khizhnyak, S.N.; Vinnikov, D.V. (Вопросы атомной науки и техники, 2009)
This paper outlines the preliminary study of a plasma components electromagnetic separator. This device is intended for separating the heavy components of spent nuclear fuel (SNF) from the light ones. The power consumed in this process is expected to comprise about 1·10³ eV per particle. We performed our experiments with the SNF simulating gas mixture. The results obtained permit to draw a conclusion that the effect of separation may be achieved.